Evaluation of an approach for the characterization of reactive and available pools of 20 potentially toxic elements in soils: part II--solid-solution partition relationships and ion activity in soil solutions - Rodrigues, S. M. (2020)
To assess environmental risks related to contaminants in soil it is essential to predict the available pool of inorganic contaminants at regional scales, accounting for differences between soils from variable geologic and climatic origins. An approach composed of a well-accepted soil extraction procedure (0.01 M CaCl(2)) and empirical Freundlich-type models in combination with mechanistically based models which to date have been used only in temperate regions was applied to 136 soils from a South European area and evaluated for its possible general use in risk assessment. Empirical models based on reactive element pools and soil properties (pH, organic carbon, clay, total Al, Fe and Mn) provided good estimations of available concentrations for a broad range of contaminants including As, Ba, Cd, Co, Cu, Hg, Mo, Ni, Pb, Sb, Se and Zn (r(2): 0.46-0.89). The variation of the pools of total Al in soils expressed the sorptive capacity of aluminosilicates and Al oxides at the surfaces and edges of clay minerals better than the actual variability of clay contents. The approach has led to recommendations for further research with particular emphasis on the impact of clay on the solubility of As and Sb, on the mechanisms controlling Cr and U availability and on differences in binding properties of soil organic matter from different climatic regions. This study showed that such approach may be included with a good degree of certainty for first step risk assessment procedures to identify potential risk areas for leaching and uptake of inorganic contaminants in different environmental settings.